A Comparative Study on TIBA Imputation Methods in FCMdd-Based Linear Clustering with Relational Data. (16th October 2011) - Yamamoto, Takeshi; Honda, Katsuhiro; Notsu, Akira; Ichihashi, Hidetomo
Abstract : Relational fuzzy clustering has been developed for extracting intrinsic cluster structures of relational data and was extended to a linear fuzzy clustering model based on Fuzzyc -Medoids (FCMdd) concept, in which Fuzzyc -Means-(FCM-) like iterative algorithm was performed by defining linear cluster prototypes using two representative medoids for each line prototype. In this paper, the FCMdd-type linear clustering model is further modified in order to handle incomplete data including missing values, and the applicability of several imputation methods is compared. In several numerical experiments, it is demonstrated that some pre-imputation strategies contribute to properly selecting representative medoids of each cluster.